The involvement of effector memory CD4+ T cells in mediating the impact of genus Oscillibacter gut microbiota on Alzheimer’s disease: a Mendelian randomization study - Zhang, Huachang; Wang, Yudong; Zhao, Hui; Wang, Wei; Han, Fabin (Frontiers in Aging Neuroscience, 2024)
Objective This study aimed to investigate the causal relationship between gut microbiota characteristics (207 taxa and 205 pathways) and Alzheimer’s disease and determine and quantify the role of immune cells as potential mediators. Methods Gut microbiota characteristics (207 taxa and 205 pathways) were obtained from the NHGRI-EBI GWAS Catalog project, while Alzheimer’s disease data and 731 immune cell characteristics were obtained from the IEU Open GWAS project. Two-sample Mendelian randomization (MR) was conducted to determine whether gut microbiota characteristics (207 taxa and 205 pathways) were causally related to Alzheimer’s disease. Furthermore, two-step MR was employed to quantify the proportion of the effect of immune cell characteristics mediated by gut microbiota characteristics (207 taxa and 205 pathways) on Alzheimer’s disease. Results A total of 17 immune cell characteristics were identified as potential mediators for 13 gut microbiota influencing Alzheimer’s disease, with Effector Memory CD4+ T-cell Absolute Count accounted for 8.99% of the causal relationship between genus Oscillibacter and Alzheimer’s disease. Conclusion In summary, our research confirms a causal relationship between gut microbiota and Alzheimer’s disease, with immune cells contributing to a significant portion of the effect. However, the full mediators of gut microbiota’s impact on Alzheimer’s disease remain unclear. Further investigation is warranted to explore additional potential risk factors acting as mediators.